Pyridostigmine-Induced Microcephaly - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The association of high-dose pyridostigmine (PYD) during pregnancy with microcephaly and CNS injury in an infant is reported from the Children's Hospital Los Angeles, CA.